Body Dysmorphic Disorder in Patients Seeking Abdominoplasty, Rhinoplasty, and Rhytidectomy. Issue 2 (February 2016) - de Brito, Maria José Azevedo; Nahas, Fábio Xerfan; Cordás, Táki Athanássios; Tavares, Hermano; Ferreira, Lydia Masako
Abstract : Background: Body dysmorphic disorder may negatively affect self-perception of body shape and lead patients to seek cosmetic surgery. This study estimates the level of body dissatisfaction and prevalence of body dysmorphic disorder symptoms in candidates for three plastic surgical procedures. Methods: Three hundred patients of both sexes divided into three groups (abdominoplasty, n = 90; rhinoplasty, n =151; and rhytidectomy, n =59) were classified as having ( n =51, n =79, and n =25, respectively) or not having ( n =39, n =72, and n =34, respectively) body dysmorphic disorder symptoms, based on the Body Dysmorphic Disorder Examination, which was administered preoperatively. Results: Prevalence rates of body dysmorphic disorder symptoms in the abdominoplasty, rhinoplasty, and rhytidectomy groups were 57, 52, and 42 percent, respectively. Significant between-group differences were observed regarding age ( p < 0.001), body mass index ( p = 0.001), and onset of body dysmorphic disorder symptoms ( p < 0.001). Within-group differences in body dysmorphic disorder severity were observed in the abdominoplasty ( p < 0.001), rhinoplasty ( p < 0.001), and rhytidectomy ( p = 0.005) groups. Body dysmorphic disorder severity was significantly associated with degree of body dissatisfaction (mean Body Dysmorphic Disorder Examination total scores; p < 0.001), avoidance behaviors ( p < 0.001), sexual abuse ( p = 0.026), suicidal ideation ( p < 0.001), and suicide attempt ( p = 0.012). Conclusions: Abdominoplasty candidates showed the highest prevalence; rhytidectomy candidates exhibited the highest percentage of severe cases, and rhinoplasty candidates had the lowest percentage of severe cases.